Improvement in reproductive efficiency in farm camels under hot arid region - SAHANI, M S; VYAS, SUMANT; JADHAV, AMINUDEEN (The Indian Journal of Animal Reproduction, 2023)
Number of matings during the follicular cycle and data on conception rate were collected and analysed in indigenous camels (Bikaneri, Jaisalmeri and Kachchhi breeds) managed under semi-intensive system. Ovarian activity during breeding and nonbreeding season was examined ultrasonographically. It was revealed that follicular growth and regression is a gradual and sequential process in absence of ovulation. Apart from breeding season follicular growth was also observed in 50 percent of the camels during non-breeding season. The mean conception percentage under single mating, 2 matings at an interval of 24 and 48 hours from 1991- 92 to 1997-98 did not show significant variation in Bikaneri, Jaisalmeri and Kachchhi breed with conception of 60.14, 53.12 and 56.94 percent respectively and a over all conception of 56.85 percent, where as the mean percent conception with 2 matings at 72 hrs interval during the follicular cycle in Bikaneri, Jaisalmeri and Kachchhi was 80.0, 72 and 71.43 percent respectively with overall conception 75.8 percent. An improvement of about 10 to 15 percent could be observed in conception rate when given 2 matings at interval of 72 hours as compared to single mating and 2 matings at an interval of 24 to 48 hours.